Subjective uncertainty and limbic hyperactivation in obsessive‐compulsive disorder - Stern, Emily R. (Hum Brain Mapp, 2012)
Obsessive‐compulsive disorder (OCD) is often associated with pathological uncertainty regarding whether an action has been performed correctly or whether a bad outcome will occur, leading to compulsive “evidence gathering” behaviors aimed at reducing uncertainty. The current study used event‐related functional magnetic resonance imaging to investigate neural functioning in OCD patients and controls as subjective certainty was rated in response to sequential pieces of evidence for a decision. Uncertainty was experimentally manipulated so that some decisions were associated with no “objective” uncertainty (all observed evidence pointed to one correct choice), whereas other decisions contained calculable but varying levels of objective uncertainty based on displayed probabilities. Results indicated that OCD patients differed from controls on decisions that contained no objective uncertainty, such that patients rated themselves as more uncertain. Patients also showed greater activation in a network of brain regions previously associated with internally‐focused thought and valuation including ventromedial prefrontal cortex, parahippocampus, middle temporal cortex, as well as amygdala and orbitofrontal cortex/ventral anterior insula. In the patient group, a significantly greater number of positive intersubject correlations were found among several of these brain regions, suggesting that this network is more interconnected in patients. OCD patients did not differ from controls on decisions where task parameters led to uncertainty. These results indicate that OCD is associated with hyperactivation in a network of limbic/paralimbic brain regions when making decisions, which may contribute to the greater subjective experience of doubt that characterizes the disorder. Hum Brain Mapp, 2013. © 2012 Wiley Periodicals, Inc.